THE EFFECTIVENESS OF THE EDMODO BASED SELF-COMPETENCY TEST TO IMPROVE STUDENT'S SELF-CONFIDENCE ON MOMENTUM AND IMPULSE MATERIALS - Arini, Dinni (Journal of Learning and Technology in Physics, 2023)
This study aims to analyze whether the computer-based self-test program can increase students' self-confidence in physics subjects and analyze whether the computer-based self-test program developed can increase effectiveness in processing competency test results accurately, practically and effectively. This research is a research and development with the development process using the ADDIE model which includes the stages, namely; Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study were students of SMA Muhammadiyah Medan. The instruments used are testing aspects of functionality, usability, and student self-confidence questionnaires. Based on the results of expert validation on the functionality test, a percentage of 94.15% was obtained with very good criteria and already met the functionality aspect, the results of expert validation on the usability test obtained a percentage of 93.65% with very high criteria and already met the usability aspect. Furthermore, the percentage of students' self-efficacy questionnaires/questionnaires is 82.15% with very high criteria